Data Sharing Drives Positive Outcomes: What Social Services Agencies Need in the Opioid Battle. - Winkler, Denise (Policy & Practice (19426828), 2018)
The article discusses the need for public and private systems in the U.S. to share information while tackling opioid addiction. According to author, sharing of data allows the addict as well as his or her family to have better life by providing matching of services in a better manner across various systems.